JERZY STARNAWSKI AS A SCHOLAR OF OLD POLISH LITERATURE – REFLECTIONS ON THE CENTENARY OF HIS BIRTH - Kuran, Michał (Prace Polonistyczne, 2022)
Having briefly outlined a vast panorama of Jerzy Starnawski’s research interests, the article describes his academic achievements in the area of the study of Old Polish literature. As will be shown, Starnawski published a wide variety of texts, such as: synthetic epoch analyses, monographs, extensive problem studies, and short articles. He also worked on critical editions. In his study of Polish and Latin literatures, Starnawski used several research methods: the philological, comparative, and biographical methods. His scholarly achievements cover medieval literature (especially hagiography), the Renaissance and Baroque, neo-Latin studies, and the European ties of Old Polish literature, the history of literature, as well as editorial achievements. The relationship between antiquity and the Old Polish literature is a recurrent issue addressed in all of his texts. Starnawski’s research focuses on the works of: Mikołaj Rej, Marcin Bielski, Stanisław Orzechowski, Szymon Starowolski, Maciej Kazimierz Sarbiewski, and, to a lesser extent, Andrzej Frycz Modrzewski, Jan Kochanowski, Piotr Skarga, Jakub Wujek, Konstancja Benisławska, and Elżbieta Drużbacka, and, in the last years of his life, Knobelsdorf and Marcin Kromer. In the final part of the article, the author discusses the academic reception of his scholarly output, based on the data from the Google Scholar citation counter.